Improving the performance of µED-milling using assisting electrode for fabricating micro-channels in CFRP composites. (2020) - Dutta, Hrishikesh; Debnath, Kishore; Sarma, Deba Kumar
Abstract: Micro-electrical discharge milling (µED-milling) is an emerging non-traditional material removal process used to fabricate micron-size features in the materials which are difficult to machine by the traditional machining process. Carbon fiber-reinforced polymer (CFRP) is one such material which is not compatible with the traditional micro-machining process due to excessive damage to the machined surface in terms of fiber breakage, delamination, fiber pull-out, etc. These types of damages mostly occur due to the mechanical interaction between the tool and workpiece. Also, fabricating features of micron size in CFRP using µED-milling is a challenging task due to its low electrical conductivity. In this research endeavor, an attempt was made to improve the performance of µED-milling with the aid of a conductive copper foil as assisting electrode to initiate the sparking between the tool and work surface. Taguchi's L9 experimental design was applied considering three input parameters namely input energy (1.805, 18.05, and 180.5 µJ), tool speed (300, 400, and 500 RPM), and EDM feed (2, 3, and 4 µm/s). The regression analysis was performed to understand the effect of the input factors on the deviation in channel width (DCW ). The profiles of the fabricated microchannels were studied under an optical microscope. The detailed morphology of the machined surface was analyzed using field emission scanning electron microscope (FESEM).